Transtracheal jet ventilation: a life-threatening or life-saving device - Selzer, Jon; Doblar, Dennis D.; Anayiotos, Andreas (My University, 1999)
Jet ventilation through the trachea can cause airway injury and death due to high airway pressure and tension pneumothorax. Intratracheal and intrapulmonary pressures developed in a lung/trachea simulator were measured using a commercial transtracheal jet ventilator coupled with a commercial 12-gauge IV catheter. Intrapleural pressures ranged from 0 to 55 cmH2O as the jet driving pressure was varied from 10 to 54 psi. Simultaneous intratracheal pressures ranged from 4 to 328 cm H2O over the same range of driving pressures. Driving pressure was a linear function of nozzle pressure over a range from 15 to 54 psi. Extreme caution must be exercised when selecting an untested catheter for use with the jet ventilator to minimize the risk of barotrauma. Testing should be performed before placing catheter-jet systems into use.
Keywords: Catheters; Respirators; Pneumothorax; Membranes (Biology)